MEDICAL STORE MANAGEMENT AT ABVGMC VIDISHA (MP): AN ANALYSIS AT TERTIARY CARE HOSPITAL - JAIN, SUDHIR KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to perform a qualitative and quantitative comparison of the practice and infrastructure with applicable legislations governing hospital pharmacy while the secondary objective was to calculate the average dispensing time of a prescription in the hospital pharmacy. Methods: Our hospital was established in 2018. A prospective cross-sectional analytic study was carried out in the hospital pharmacy for 6 months (January 23–June 23). A blend of quality control parameters was drafted after referring various guidelines put forward by the statutory bodies. Qualitative data were collected by continuous observation, physical inspection, and after a thorough interview of hospital pharmacists. The collected data were summarized and compared with the standards. Quantitative data on the minimum requirement of hospital pharmacy infrastructure and dispensing time were collected using the designed data collection form and analysis was performed. Results: The hospital pharmacy met all the criteria that are necessary to satisfy legal requirements, availability of medicine, medicine, and general safety, and most of the quality parameters. However, few deviations were observed in the management of the drug store. The shortage in the floor space and waiting area was identified. In the study, we find that the average waiting time for the patient at the drug distribution center is 180 s and the average drug dispensing time was 130 s. On the basis of our good working in pharmacy, we got NABH approval in 2023 which includes pharmacy with other departments of this hospital. Conclusion: Majority of the quality parameters were noted to be compliant with the standards. Few deviations were identified and measures to improve them were suggested.